Temperature-dependent degradation of Al2O3—CrAl-O—Cr-O—Al-O multilayer coatings on ferritic-martensitic steels in oxygen-saturated lead–bismuth eutectic - Jiaojiao Ma; Lili Xing; Jie Tan; Hui Wang; Xiujie He; Xing Yin (Materials & Design)
The strong corrosiveness of lead–bismuth eutectic (LBE) to alloys significantly limits the development of lead-cooled fast reactors. Herein, a multilayer coating containing Al-O, Cr-O, CrAl-O, and Al2O3 layers were deposited on ferritic–martensitic steel using magnetron sputtering and tested in oxygen-saturated LBE at 450, 550, and 650 °C for 2000 h. The phase transformation and microstructural evolution of the coating, owing to temperature and element diffusion, were characterized in detail at the microscale. At 450 °C, the Al2O3 layer partially transformed to δ*-Al2O3 and PbAl2O4, while the Cr-O layer crystallized into Cr2O3. At 650 °C, γ-Al2O3 transitioned to α-Al2O3, and a dense α-(Cr,Al)2O3 phase formed at the CrAl-O/Al2O3 interface, effectively blocking LBE penetration. Despite full infiltration of the Al2O3 layer at 650 °C, the CrAl-O interlayer suppressed elemental interdiffusion, maintaining substrate integrity. Temperature-dependent degradation revealed critical failure at the Cr-O layer due to MnCr2O4-induced porosity. The multilayer coating maintained a relatively good integrity at high temperatures and protected the substrate from LBE corrosion.